A rare γ-pyranopyrazole skeleton: design, one-pot synthesis and computational study. Issue 31 (13th July 2016) - Üçüncü, Muhammed; Cantürk, Ceren; Karakuş, Erman; Zeybek, Hüseyin; Bozkaya, Uğur; Soydaş, Emine; Şahin, Ertan; Emrullahoğlu, Mustafa
Abstract : A base mediated one-pot, two-step synthetic method for constructing γ-pyranopyrazoles. Abstract : Drawing upon a consecutive amide coupling and intramolecular cyclisation pathway, a one-pot, straightforward synthetic route has been developed for a range of pyrazole fused γ-pyrone derivatives. The reaction mechanism proposed for the chemoselective formation of γ-pyranopyrazole is furthermore fully supported by experimental and computational studies.